Development of graphene oxide – PDMS composite dielectric for rapid droplet movement in digital microfluidic applications. (2nd February 2021) - Basu, Mainak; Parihar, Vartika; Lincon, Abhijit; Joshi, Vedant P.; Das, Soumen; DasGupta, Sunando
Graphical abstract: Highlights: Addition of graphene oxide in PDMS results in interfacial polarization. Substantial improvement in the electrical properties of GO-PDMS composite. Rapid droplet manipulation at lower actuation voltages using GO-PDMS as dielectric. Abstract: Dielectric breakdown puts an operating limit to the applied electric field in electrowetting-based applications. Herein, we report that the electrical properties relevant to electrowetting for a widely used dielectric, PDMS, can be substantially enhanced upon the incorporation of graphene oxide (GO) fillers into the PDMS polymer matrix. The GO-PDMS composite is characterized by higher values of the dielectric constant, higher breakdown electric field, and lower actuation voltages due to enhanced interfacial polarization. The improvement of these properties with the increase in concentration of GO, is explored till the 'percolation threshold'. This newly developed composite as the dielectric, droplet actuation and electric field-induced droplet transportation over a fabricated triangular electrode system are performed. The results are compared with the literature data on PDMS and other dielectrics to establish the superior qualities of the dielectric for rapid transportation of droplets at significantly lower voltages with potential for new applications.